2005
DOI: 10.1157/13078032
|View full text |Cite
|
Sign up to set email alerts
|

Riesgos competitivos de muerte y equilibrio de Hardy-Weinberg en estudios de casos y controles sobre asociación entre genes y enfermedades

Abstract: Although the main causes of Hardy-Weinberg disequilibrium in controls are selection bias or genotyping error, a competing risk of death associated with the mutant gene would also result in Hardy-Weinberg disequilibrium among controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 6 publications
0
5
0
3
Order By: Relevance
“…Meanwhile, Galbiatti et al also reported that polymorphism of CBS gene was not in Hardy-Weinberg equilibrium [26] . The departure from the Hardy-Weinberg equilibrium may result from selection bias, disease model adopted, and evolutionary factors which may influence changes in the genotype frequencies [35] , [36] . On the other hand, this disequilibrium should be expected, in the case that it reflected biological and genetic characteristics in complex disease models [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Galbiatti et al also reported that polymorphism of CBS gene was not in Hardy-Weinberg equilibrium [26] . The departure from the Hardy-Weinberg equilibrium may result from selection bias, disease model adopted, and evolutionary factors which may influence changes in the genotype frequencies [35] , [36] . On the other hand, this disequilibrium should be expected, in the case that it reflected biological and genetic characteristics in complex disease models [37] .…”
Section: Discussionmentioning
confidence: 99%
“…The departure from the HWE may result from the random selection of the studied individuals, the disease model adopted, and evolutionary factors which can influence changes in the genotype frequencies [34, 35]. On the other hand, this disequilibrium should be expected, considering that it reflects biological and genetic characteristics in complex disease models [36].…”
Section: Discussionmentioning
confidence: 99%
“…En cambio, las alteraciones de baja penetrancia necesitan, para manifestarse, la participación de otros procesos, fundamentalmente ambientales. Decimos así que las interacciones con el medio ambiente son intrínsecas al modo de actuación de los genes de baja penetrancia: las alteraciones en estos genes permanecen «silenciosas» o «mudas» hasta que algún factor externo las hace «despertar» y expresarse [1][2][3][4][5][6] .…”
unclassified
“…Puesto que son infrecuentes, las alteraciones más penetrantes sólo causan una proporción pequeña de los casos de las enfermedades más prevalentes en nuestras sociedades [1][2][3][4] . La inmensa mayoría de estas enfermedades son el resultado de acumular durante años alteraciones genéticas somáticas, tras complejas interacciones entre múltiples genes, sus productos (sus proteínas) y una diversidad de procesos socioambientales [5][6][7][8] ; entre estos últimos podemos mencionar la exposición crónica, a dosis generalmente bajas, a agentes químicos ambientales (AQA), genotóxicos o no 7-10 .…”
unclassified
See 1 more Smart Citation